دلالة الموت في ديوان نبض الفجيعة لحسن خراط - كعوان، سامية Kawan, Samiah (جامعة عمار ثليجي بالأغواط, 2017)
حاول الشاعر الجزائري أن يساير تغيرات المجتمع فكانت المواضيع التي تطرق لها ذات صلة بواقعه حيث كثر الاهتمام بمشاعر الإنسان، فبأسلوب رمزي استطاع أن يعكس القلق، الخوف، والغموض، وذلك من خلال تيمة الموت. \ وتهدف دراستنا هذه إلى إبراز تجليات الموت ودلالته في الخطاب الشعري عند حسن خراط، من خلال: العنوان وخطاب الموت، تجليات موت الوطن، موت الحيوان ودلالته، الإنسان وفجيعة الموت، إن خطاب الموت كان متعدد الأبعاد والدلالة، تنوعت عبره رؤية الكاتب.
The Algerian poet tried to keep up with the changes of the society. The subjects he dealt \ with were related to his reality. There was a great deal of interest in human feelings, in a symbolic \ way that reflected anxiety, fear and mystery through the theme of death. The purpose of this study \ is to highlight the manifestations of death and its significance in the poetic discourse of Hassan \ kharat, through: the title and speech of death, the manifestations of the death of the homeland, the \ death of the animal and its significance, man and the horror of death. The speech of death was \ multidimensional and meaningful
Keywords: الشعر العربي -- الشعراء الجزائريون -- خراط ، حسن -- نقد الشعر -- الدواوين والقصائد -- ديوان نبض الفجيعة -- الموت -- مستخلصات الأبحاث